Brownian motion in duct of periodic varying radius: external driving force and particle mobility - Miguel, A. F. (2018)
This study is about how a uniform driving force affects the particle motion in periodic entropy potentials. Results available in the literature show that particle mobility, in a cylindrical tube, is independent of the driving force. For a regular periodic potential, effective mobility increases monotonically with the driving force. Does the driving force have the same effect in a periodic entropy potential? In this paper, a duct that consists of a set of cylindrical compartments is considered. We find that the effective mobility decreases monotonically with the external driving force.